Ֆրանսիական հետքեր Կիլիկիայի հայոց արքաների թագադրման ծեսում - Թորոսյան, Վահե
The coronation ordo of the Armenian Kingdom of Cilicia, preserved in the Hayr Mashtoc (the Book of Rituals of the Armenian Church), is based on the coronation ordo of the Holy Roman Empire, specifically the Mainzer Krönungsordo of the Ottonian kings. The Cilician ordo is titled “Order of a King’s Consecration Service according to the Great Church of Rome”. It was translated from Latin into Armenian by the prominent 12th-century ecclesiastical figure Nerses Lambronatsi in 1190. This translation was later revised and adapted to align with the administrative and political system of the Armenian Kingdom, as well as the rites and creed of the Armenian Church. Notably, the coronation ordo of the Armenian Kingdom of Cilicia includes a royal oath, a feature that is unique to the Armenian and French ordos. Interestingly, a royal oath is absent from the coronation ordo of the Holy Roman Empire, the source text for the Cilician rite. Moreover, the Armenian ordo shares similarities in content and in structure with the French coronation ordo of the 13th century. Royal oaths are found in corresponding sections of both the French and Armenian texts. Taking this into account, it seems likely that there was a French influence on the royal oath of the Armenian coronation ordo. Коронационный ритуал Армянского Киликийского царства, сохранившееся в Книге ритуалов Армянской церкви (Հայր Մաշտոց), основан на коронационном ритуале Священной Римской империи, в частности, на Майнцском Krönungsordo династии Оттонов. Киликийский ритуал озаглавлен «Порядок церемонии посвящения короля в соответствии с Великой Римской церковью». Его в 1190 году перевел с латинского на армянский выдающийся церковный деятель XII века Нерсес Ламбронаци. Этот перевод в дальнейшем отредактировали, приспособив к политико- административной системе Армянского царства, а также к ритуалам и обиходу канонам Армянской церкви. Примечательно, что в коронационный ритуал Армянского Киликийского царства входит королевская присяга. Это особенность армянского и французского ритуала. Такой присяги нет в ритуале Священной Римской империи, источнике текста киликийского ритуала. Более того, содержание армянского ритуала имеет черты, сходные с французским коронационным ритуалом XIII века․ Присяга помещена в идентичных разделах обоих текстов. Сказанное позволяет предположить, что армянский коронационный ритуал подвергся французскому влиянию.
Keywords: Պատմություն